The association between oxidative balance score and gallstones in adults: a population-based study - Yang, Yuxiao; Wang, Jia; Liu, Yuan; Yu, Jiali; Chen, Guanyu; Du, Shiyu (Frontiers in Nutrition, 2025)
PurposeOxidative stress is a significant contributor to the progression of gallstones. However, the combined or independent effects of dietary and lifestyle pro-antioxidants and antioxidants on gallstone formation remain unclear. Our study aims to investigate the potential link between the oxidative balance score (OBS) and the occurrence of gallstones.Patients and methodsThis study utilized data from the National Health and Nutrition Examination Survey (NHANES), conducted in the United States between 2017 and March 2020, identifying 750 gallstone cases among the 7,489 participants. Gallstone status was self-reported. The data in this study were analyzed using a range of statistical techniques, such as Multivariable logistic regression, restricted cubic spline curves (RCS), mediation effects analysis, subgroup analyses and sensitivity analysis.ResultsUsing fully adjusted multivariable logistic regression analysis, we identified a significant negative correlation between OBS and the occurrence of gallstones, with an odds ratio (OR) of 0.97 and a 95% confidence interval (CI) of 0.96 to 0.99. Furthermore, participants in the highest quartile of OBS exhibited a 41% reduced risk of gallstones compared to those in the lowest quartile, with an OR of 0.59 (95% CI: 0.45, 0.79) relative to the reference population. Additionally, a linear inverse association between OBS and gallstones was observed. Mediation analysis indicated that diabetes and cardiovascular diseases (CVD) mediated 3.5 and 4% of the association between OBS and gallstones, respectively.ConclusionThis research suggests that lower OBS levels are associated with a higher susceptibility to gallstone formation, potentially offering a new perspective on clinical strategies for the management and prevention of gallstones.